2013
DOI: 10.4103/1305-7456.119084
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of third molar impaction in Turkish orthodontic patients: Prevalence, depth and angular positions

Abstract: Objective:We aimed to investigate the prevalence, distribution, angular position, and depth of third molar impaction in a Turkish orthodontic patient population.Materials and Methods:We retrospectively reviewed the panoramic radiographs, intraoral photographs, and dental casts of 207 patients (62 men and 145 women; age 20-39 years) who had undergone orthodontic treatment at a university department of orthodontics for impacted third molars (ITMs). A comprehensive chart review of all subjects was conducted. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
2
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 11 publications
2
20
2
6
Order By: Relevance
“…4 Furthermore, the higher rates of impaction in the lower jaw can also be attributed to the imbalance of the bone deposition-resorption process at the mandibular ramus, resulting in either a decrease in the Pattern of third molar impaction in Libyan population angulation of the mandible or increase in the angulation of the mandibular plane. 15 On the other hand, Studies have suggested that factors like fixed orthodontic treatment which involves extraction of lower premolars followed by subsequent closure of residual spaces allowed the position of many impacted third molars to improve significantly by increasing the available space from 4 mm to 11 mm and decreasing the distance to the occlusal plane from 12 to 10 mm. 16 The minimum age of participants in this study was 20 years (mean: 29 ± 6 years).…”
Section: Discussionmentioning
confidence: 98%
“…4 Furthermore, the higher rates of impaction in the lower jaw can also be attributed to the imbalance of the bone deposition-resorption process at the mandibular ramus, resulting in either a decrease in the Pattern of third molar impaction in Libyan population angulation of the mandible or increase in the angulation of the mandibular plane. 15 On the other hand, Studies have suggested that factors like fixed orthodontic treatment which involves extraction of lower premolars followed by subsequent closure of residual spaces allowed the position of many impacted third molars to improve significantly by increasing the available space from 4 mm to 11 mm and decreasing the distance to the occlusal plane from 12 to 10 mm. 16 The minimum age of participants in this study was 20 years (mean: 29 ± 6 years).…”
Section: Discussionmentioning
confidence: 98%
“…Many researchers [3, 9, 12, 15-17] have claimed that greater mesial crown inclinations of third molars seem to be indicative of mandibular third molar impaction. Similarly, in this study, mesial inclination of the mandibular third molar and distal inclination of the maxillary third molar were found to be indicative of the tendency for these teeth to be impacted.…”
Section: Discussionmentioning
confidence: 99%
“…1 Controversies have been reported with regard to the incidence of M3 impaction related to gender, ethnicity, and location. 2 There is evidence that factors such as vertical growth pattern, reduced mandibular length, molar axial inclination, and delayed maturation may influence the likelihood of M3 eruption. 3,4 Overall, impacted maxillary third molars do not remain static; however, their position over time may be considered unpredictable, as indicated by the limited longitudinal data.…”
Section: Introductionmentioning
confidence: 99%